Exploring the Relationship between Muslimah Clothing and Religiousness: A Study on UPI Female Students: Menelusuri Hubungan Busana Muslimah dan Religiusitas: Studi pada Mahasiswi UPI - Sinta, Dewi; Syahidin, Syahidin; Nurhuda, Abid; Al Anang, Arif (Averroes: Journal for Science and Religious Studies, 2024)
Research Background: The use of Muslimah clothing has become an interesting phenomenon in recent years. This phenomenon not only serves as aurat cover according to Islamic law but also becomes part of modern fashion. This study aims to analyze the impact of using Muslimah clothing on the religiosity of female students of Universitas Pendidikan Indonesia (UPI), including aspects of aqidah, sharia, and morals. Method: This research uses descriptive quantitative approach. Data were collected through literature research and field research using Google Form questionnaires filled out by UPI female students. Main Findings: The results showed that the majority of UPI female students use Muslimah clothing with syar'i hijab and long wide hijab. The use of Muslimah clothing has a positive impact on belief (aqidah), but the impact on worship habits (sharia) and morals is still uneven. Contribution: This research provides a conceptual contribution by describing the relationship between the use of Muslimah clothing and the level of religiousness. Practical contributions in the form of views and solutions are also provided for female students who have difficulty in reaching high levels in their religiosity. Conclusion: The use of Muslimah clothing among UPI female students has a positive impact on their beliefs, but the impact on worship habits and morals still needs improvement. Future research is recommended to use a qualitative approach with a broader scope for a deeper understanding.